2021
DOI: 10.21608/jalexu.2022.111943.1029
|View full text |Cite
|
Sign up to set email alerts
|

Use of Abamectin as An Eco-Friendly Pesticide Against Diamondback Moth on Cabbage Crop

Abstract: The diamondback moth, Plutella xylostella, is the greatest damaging insect of cabbage plants. Two field experiments were conducted at private farm in El-Kattawia area, Abu-Hammad City, Sharkia Governorate, Egypt to assess the effectiveness of abamectin 1.8 EC against cabbage diamondback moth. Two field experiments were performed at the same farm in different seasons (2019 and 2020).The experiments were conducted in a randomized block design with a plot size of 4 x 5 m with three replications. The concerned tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(4 reference statements)
2
0
0
Order By: Relevance
“…The findings of this study showed that cabbage was infested by numerous insect pests, including onion thrips, T. tabaci, cabbage white butterfly, P. rapae, diamondback moth, P. xylostella, and cabbage aphids, B. brassicae. The same findings were observed in many previous studies (Abdel-samad 2010;Rahouma 2018;El-Sheikh 2020;Morsy and Elwan 2021). Also, the onion thrips, T. tabaci, was identified as a major pest of cabbage (Ngosong 2017), which was also confirmed in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study showed that cabbage was infested by numerous insect pests, including onion thrips, T. tabaci, cabbage white butterfly, P. rapae, diamondback moth, P. xylostella, and cabbage aphids, B. brassicae. The same findings were observed in many previous studies (Abdel-samad 2010;Rahouma 2018;El-Sheikh 2020;Morsy and Elwan 2021). Also, the onion thrips, T. tabaci, was identified as a major pest of cabbage (Ngosong 2017), which was also confirmed in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The study results showed that the maximum yield was found in plots treated with the chemical pesticide cypermethrin, which was followed by M. robertsii, neem oil, and B. bassiana treatments, all of which were significantly superior over others, i.e., vermiwash, L. lecanii, B. thuringiensis, and control. The treated plot with cypermethrin gave the highest yield and these results are almost in line with the findings of Morsy and Elwan [98], who reported the highest yield for cabbage. Jadhav et al [99] reported that the foliar spray of vermiwash gave a significantly higher yield.…”
Section: Discussionsupporting
confidence: 90%
“…To manage agricultural pests, Egypt uses the insecticide abamectin. A natural byproduct of soil actinomycetes is abamectin [27]. Abamectin consumption appears to be linked to intestinal intoxication and epithelial cell changes, which alter the physiology and function of the pest's alimentary canal and result in death.…”
Section: Introductionmentioning
confidence: 99%